PROGRAM PEMBANGUNAN PARTISIPATIF DAN DAMPAKNYA TERHADAP PEMBERDAYAAN MASYARAKAT - Endah Tri Anomsari; Rodlial Ramdhan Tackbir Abubakar (NATAPRAJA, 2019)
Since the Washington Consensus in the 1990s, participation has become a mainstream issue in development policy, including in Indonesia post-Political Reformation in 1998. The involvement of the community in development policy achieves moral and intellectual support so that not only national, the local-level policy also uses participatory approach as it is considered to be effective in empowering people. Using a descriptive-qualitative approach, this study is an analysis on how participation in the Development Innovation and Regional Empowerment Program (PIPPK) brings impacts to empowerment of Bandung communities. According to data gathered in Bandung, participation cannot bring empowerment instantly. PIPPK has encouraged empowerment in terms of capability expansion, but it has not brought changes in opportunity structure. There are two main factors which leads to the results, those are: (1) that empowerment is complex, multidimensional, and continuous so that it is challenging to explore to what extent empowerment has progressed and (2) that the participation of people in PIPPK is restricted to the program implementation and not yet reflect the citizen power.Keyword: development, empowerment, community participation, participatory approach